2013
DOI: 10.4236/ojst.2013.38073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an oral moisture-checking device for screening dry mouth

Abstract: Objective: This multicenter clinical study was to assess the clinical usability of an oral moisturechecking device in detecting the dry mouth patients and evaluating the optimal measurement site. Materials and Methods: The study group comprised 250 patients with dry mouth and 241 healthy volunteer subjects at 13 medical centers. This device was used to measure the moisture degrees of the lingual mucosa and the buccal mucosa. Subjective oral dryness, objective oral dryness, and saliva flow rates were also compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…In this study, the oral moisture checker was applied to measure the moisture of the submucosal layer at the central tongue dorsum linguae, 10 mm backward from the apex linguae. The oral moisture checker has been validated; Fukushima et al reported that 241 participants with dry mouth showed 27.2 ± 4.9, while 250 participants without dry mouth showed 29.5 ± 3.1. The cut‐off value is 27.0, that is a measured value <27.0 is evaluated as OD .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the oral moisture checker was applied to measure the moisture of the submucosal layer at the central tongue dorsum linguae, 10 mm backward from the apex linguae. The oral moisture checker has been validated; Fukushima et al reported that 241 participants with dry mouth showed 27.2 ± 4.9, while 250 participants without dry mouth showed 29.5 ± 3.1. The cut‐off value is 27.0, that is a measured value <27.0 is evaluated as OD .…”
Section: Methodsmentioning
confidence: 99%
“…When evaluating these conditions, an oral moisture checker is suitable for quantitatively assessing the amount of moisture at the measuring site. The device has demonstrated that the amount of moisture in intraoral soft tissue is correlated with the amount of salivary secretion and has shown good results pertaining to sensitivity and specificity in screening for individuals with decreased salivary secretion …”
Section: Concept Of Signs and Symptoms Constituting Oral Hypofunctionmentioning
confidence: 99%
“…The value strongly correlates positively with the actual gravimetric moisture percentage, with a correlation coefficient of 0.99, and is a relative measure of water content, rather than the actual moisture percentage. To perform measurements, a sensor of this device was brought into vertical contact with the surface of the tongue 10 mm from the tip of the tongue . Measurement was performed three times, and the median value was used.…”
Section: Methodsmentioning
confidence: 99%